Pengaruh Marketing Mix Terhadap Repurchase Intention dengan Customer Satisfaction Sebagai Variabel Intervening pada Cafe Lou Space di Makassar - Suyatno Karim; Hety Budiyanti; Ilma Wulansari Hasdiansa; Muhammad Ilham Wardhana Haeruddin; Rahmat Riwayat Abadi (PT Maju Malaqbi Makkarana, 2026)
Amidst the increasingly tight competition in the cafe business, cafe owners are implementing suitable strategies for their cafes. This study aims to determine the effect of the marketing mix on repurchase intention with customer satisfaction as an intervening variable at Lou Space cafe in Makassar. This study uses a quantitative approach that is explanatory in nature. The population in this study are Lou Space consumers in Makassar. The sampling technique uses non-probability sampling with a purposive sampling method. The sample used is 200 respondents. Data were collected through questionnaires and data analysis techniques were carried out using the Structural Equation Model Partial Least Square (SEMPLS) with the help of SmartPLS 3.0 software. The results of the study indicate that (1) Product, Price Perception, Place, Promotion have a positive and insignificant effect on Repurchase Intention (2) Product, Price Perception, Place, Promotion have a positive and significant effect on Customer Satisfaction (3) Customer Satisfaction have a positive and significant effect on Repurchase Intention (4) Product, Place Promotion have a positive and significant effect on Repurchase Intention through Customer Satisfaction (5) Price Perception have a positive and insignificant effect on Repurchase Intention through Customer Satisfaction. The conclusion in this study shows the importance of an effective marketing strategy to increase customer satisfaction and loyalty. The implications of this research can be a reference for Cafe Lou Space management in designing a marketing strategy that is more oriented towards customer satisfaction to increase repurchase intention.